PENINGKATAN MOTIVASI KERJA GURU DENGAN MENGGUNAKAN METODE DISKUSI OLEH KEPALA SEKOLAH DI SMAN 1 LANGGAM KABUPATEN PELALAWAN PROVINSI RIAU TAHUN PELAJARAN 2021/2022 - SRI MARTATI (JURNAL ILMIAH SIMANTEK, 2022)
The principal is a teacher professional who is given the task of leading an organization or an institution. problems related to teacher work motivation where teachers are less enthusiastic in carrying out the teaching and learning process. The purpose of this study was to describe the principal's efforts to increase teacher motivation using the group discussion method at SMAN 1 Langgam, Pelalawan District. The type of research used in this research is the school action research method (PTS). Location The research was conducted at SMAN 1 Langgam, Pelalawan District, Riau Province. Time The research will be carried out in the second semester of January-June for the 2021/2022 school year. The subjects of the principal's action research were 19 teachers at SMAN 1 Langgam. The technique of collecting data from this school action research is through quantitative data obtained from observation and interviews. The data analysis technique used in this study is quantitative data analysis originating from the acquisition of the instrument. Based on the results of the study, it can be concluded that the principal's efforts to increase teacher motivation by using the discussion method from the results of the first cycle of the second meeting obtained an average success in increasing teacher motivation in learning only reached 65%, because the teacher had not been successful in cycle I continued in cycle II, in this II by using the method of group discussion teacher motivation increased to 96%. because the results of the findings were in accordance with what was expected, the research was stopped in cycle II, there was an increase in teacher motivation by 31%.